A critique of Koh's (2014) 'Doing class analysis in Singapore's elite education'. (15th March 2017) - Kabel, Scott
ABSTRACT: Aaron Koh contributed to a collection of multi-site global ethnographic articles published here (2014, Vol. 12, No. 2) that present class reproduction as operationalised in elite education. While the collection adds to the current international critique of meritocracy, a close look at Koh's contribution reveals that critical ethnography can lose its representational and persuasive power if muddled by theoretical and methodological haziness and if it fails to forefront participants' voices. This response is meant to encourage Koh to re-present his data and position so as to sure up his comment on this important issue.